The strength of the weakest link: Sickness absence, internal substitutability and worker-firm matching - Lena Hensvik; Olof Rosenqvist (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
We study how employee sickness absence affects worker-firm matching. We build on the idea that firms are sensitive to absence in jobs with few substitutes (unique positions). Consistent with this, we show that unique employees are less absent conditional on individual characteristics, establishment fixed effects and detailed occupational information. Half of this association is explained by sorting of low-absence workers into unique positions but sorting is less pronounced under imperfect information. Finally, job separations respond more to realized sickness absence in unique positions. The findings suggest that the cost of production disruptions is an important aspect of firms' hiring choices.
Keywords: J23; J24; L23; M51; 330; sickness absence; production disruption; coworker substitutes; hiring strategies